?A STUDY OF DEVIATION FROM LOCAL THERMODYNAMIC EQUILIBRIUM IN THER- MAL PLASMAS BY OPTICAL EM~SSIONSPECTROSCOPY (Biological Sciences - PJSIR, 1998)
A fast, accurate and comprehensive optical emission spectroscopic set-up has been employed to investigate the devia- tion from local thermodynamic equilibrium in a 75-ampere argon plasma arc. The HIIand H" lines of hydrogen were monitored with a spectrograph while an Ar Iline and its neighbouring continuum were simultaneously monitored with a monochromator. The electron number densities calculated from Stark-broadened H~and H" lines of hydrogen were compared with those derived from absolute intensity measurements of the 7635 A Ar l line. The Ha line showed an order-of-magnitude higher number density than LTE measurements; the Ha results are generally known to be inaccurate because this line is self-absorbing and its refined Stark-broadening parameters have not been calculated. The H~line is usually the first choice for Stark-broadening calculations; its theory is well developed, and results are expected to be accurate within 10%. Results from the H~line turned out to be about 4 times higher than LTE results. This difference is attributed to two possible reasons: first, the strong Ar Iline also suffers from self-absorption and second, there may be a considerable deviation from LTE.